The Spectral Properties of the Bright Fast Radio Burst Population - Macquart, Jean-Pierre; Shannon, Ryan; Bannister, K.W.; James, Clancy; Ekers, Ronald; Bunton, J.D. (2019)
We examine the spectra of 23 fast radio bursts (FRBs) detected in a fly's-eye survey with the Australian SKA Pathfinder, including those of three bursts not previously reported. The mean spectral index of α = -1.5 -0.3+0.2 (Fv ∞ v α) is close to that of the Galactic pulsar population. The sample is dominated by bursts exhibiting a large degree of spectral modulation: 17 exhibit fine-scale spectral modulation with an rms exceeding 50% of the mean, with decorrelation bandwidths (half-maximum) ranging from ≈1 to 49 MHz. Most decorrelation bandwidths are an order of magnitude lower than the ≳30 MHz expected of Galactic interstellar scintillation at the Galactic latitude of the survey, |b| = 50° ± 5°. However, these bandwidths are consistent with the ∼v 4 scaling expected of diffractive scintillation when compared against the spectral structure observed in bright UTMOST FRBs detected at 843 MHz. A test of the amplitude distribution of the spectral fluctuations reveals only 12 bursts consistent at better than a 5% confidence level with the prediction of 100%-modulated diffractive scintillation. Five of six FRBs with a signal-tonoise ratio exceeding 20 are only consistent with this prediction at less than 1% confidence. Nonetheless, there is weak evidence (92%-94% confidence) of an anti-correlation between the amplitude of the spectral modulation and dispersion measure (DM), which suggests that it originates as a propagation effect. This effect is corroborated by the smoothness of the higher-DM Parkes FRBs, and could arise due to quenching of diffractive scintillation (e.g., in the interstellar medium of the host galaxy) by angular broadening in the intergalactic medium.